Awareness and Preventive Practices related to Cervical Cancer among Women in Pokhara Metropolitan City - Dhakal, Rojana (NPRC Journal of Multidisciplinary Research, 2026)
Background: Cervical cancer is primarily caused by persistent infection with the human papillomavirus (HPV) and is considered one of the most preventable forms of cancer. Early detection through regular screening is essential, as it enables the identification of precancerous cervical cell changes and allows for timely intervention and treatment. This study aims to assess the level of knowledge regarding cervical cancer screening and its utilization.Methods: This study employed a descriptive cross-sectional design and was conducted among 464 married women residing in Ward No. 13 of Pokhara Metropolitan City. Participants were selected using a purposive sampling technique. Data were collected through face-to-face interviews using a structured questionnaire that included items on demographic characteristics, reproductive history, awareness of cervical cancer and its screening, and the utilization of screening services.Results: A total of 464 married women participated in the study. Among them, 419 (90.3%) had heard of cervical cancer. Among those who had heard of cervical cancer, 377 (90%) demonstrated poor awareness of cervical cancer and its screening. Only 82 women (17.7%) had undergone cervical cancer screening, and among those screened, 50 (61%) reported having a Pap smear test. The most commonly reported reason for not undergoing screening was the absence of perceived health problems, followed by inadequate knowledge about the test. Factors such as educational status, occupation, age at marriage, parity, and age of childbirth showed a significant association with screening awareness.Conclusion: Although most participants had heard of cervical cancer, the overall level of awareness was poor, and the utilization of screening was low. Targeted culturally sensitive educational interventions and awareness programs are needed to improve knowledge and promote regular cervical cancer screening among married women.